The Analysis of Scientific Approach in Thematic Learning Using Webbed Model in Ambawang River State Elementary School - Kusrini Kusrini (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2019)
The problems of this research focused on the planning, implementation and obstacles of applying a scientific approach to thematic spider web learning models, aiming at making learners more active, critical thinking, the direct process experienced by the learners, the learning could be more meaningful, contextual and fun. This research was conducted at  SDN (State Elementary School) 07 and  SDN 36 at Sungai Ambawang District. It is descriptive qualitative research. The subjects of this research were the educators and the students of grade IV at SDN 07 and SDN 36 of Sungai Ambawang District. The techniques of data collection used were observation, interview, and documentation study. Data analysis was conducted through the steps: data reduction, data display, and conclusion. The technique for examining data validity was by triangulation. The results revealed that the educators had implemented the scientific approach on the thematic spider web learning model. The scientific approach implemented, includes: (1) observing, (2) questioning, (3) trying, (4) reasoning, and (5) communicating. The obstacles encountered in this lesson were lack of adequate facilities and infrastructure, the ability of their educators in mastering the learning strategy, and the low-level participation of some parents who were less concerned about their children's education and also the different characteristics of the learners.